Jesus in America - Gould, Claudia (Utah State University, University Libraries, 2009)
Claudia Gould draws on fieldwork she conducted, as an anthropologist, in North Carolina, where she earlier spent large parts of her childhood, among a net of paternal relations. From that ethnography and from lifelong observation, she crafts stories that lay open the human heart and social complications of fundamentalist Christian belief. These stories and the compelling characters who inhabit them pull us into the complicated, variable core of religious experience among southern American Christians. Jesus in America, a perceptive work rich with cultural insight, is a singular addition to the growing genre of ethnographic fiction.